2022
DOI: 10.1007/s11104-021-05251-x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal phosphorus and nitrogen cycling in four Japanese cool-temperate forest species

Abstract: Purpose In plant-soil systems, phosphorus partitioning during the annual cycle related to nitrogen partitioning remains largely unknown. The present study aims at assessing the soil-plant P allocation patterns of four tree species along four phenological stages and its relationship with tissues and soil N concentrations. Methods Cryptomeria japonica, Larix kaempferi, Fagus crenata and Robinia pseudoacacia trees were selected to sample coarse roots, sapwood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…With the increasing use of N fertilizers after reclamation, soil acidity was induced, leading to a decrease in the rate of SOM decomposition and favoring soil C accumulation [54]. Moreover, N additions could promote organisms to produce more extracellular phosphatase enzymes that cleave ester-P bonds in soil organic matter, thereby increasing P availability for crop uptake [64,65]. Although farmers tend to apply chemical P fertilizers, these compounds are less mobile and are poorly utilized during the crop season (less than 30% of total fertilization) [9].…”
Section: Effects Of Reclamation Duration On Soil C N and P Contents A...mentioning
confidence: 99%
“…With the increasing use of N fertilizers after reclamation, soil acidity was induced, leading to a decrease in the rate of SOM decomposition and favoring soil C accumulation [54]. Moreover, N additions could promote organisms to produce more extracellular phosphatase enzymes that cleave ester-P bonds in soil organic matter, thereby increasing P availability for crop uptake [64,65]. Although farmers tend to apply chemical P fertilizers, these compounds are less mobile and are poorly utilized during the crop season (less than 30% of total fertilization) [9].…”
Section: Effects Of Reclamation Duration On Soil C N and P Contents A...mentioning
confidence: 99%
“…Nutrient limitation of plant growth and productivity is widespread in global terrestrial ecosystems (LeBauer and Treseder, 2008;Hou et al, 2020). Root uptake and leaf nutrient resorption are two main mechanisms used by plants to acquire and conserve nutrients, respectively (Cleveland et al, 2013;Brant and Chen, 2015;Seidel et al, 2022). Nutrient resorption from senescing leaves is an important nutrient conservation strategy for perennial plants (Aerts, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This is especially important in nutrient-limited ecosystems, where nutrient resorption could make plants rely less on external soil nutrient supply (Kobe et al, 2005). Aerts (1996) showed that about 50% of nitrogen (N) and 52% of phosphorus (P) in green leaf were resorbed by global perennial plants, and they can contribute 31% to 40% of the annual plant N and P demand, respectively (Cleveland et al, 2013;Seidel et al, 2022). Although previous studies focus mainly on nutrient resorption from leaves, a comparable amount of nutrients can also be recycled via resorption by other plant organs such as root, twig and stem (Brant and Chen, 2015;Chen et al, 2015;Veneklaas, 2022).…”
Section: Introductionmentioning
confidence: 99%